Integrasi Psikolinguistik dalam Pembelajaran Bahasa Arab: Pendekatan Behaviorisme, Mentalisme, Kognitifisme, Konstruktvisme dan Nativisme - Nismawati, Nismawati; Darmawati, Darmawati (STAINI Press, 2025)
The background of the problem discussed in this article relates to a deep understanding of various schools of thought within psycholinguistics, namely behaviorism, cognitivism, mentalism, constructivism, and nativism. Each of these approaches provides different perspectives on how language processes occur and how individuals learn languages. In the context of language learning, particularly Arabic, understanding these theories is crucial for designing effective teaching methods. This article aims to provide a comprehensive overview of the dynamics of psycholinguistic theories and their relevance in the study of the Arabic language today. The research employs a qualitative descriptive approach through literature study (library research), analyzing and summarizing key theories and relevant findings. The analysis results indicate that the behaviorist approach emphasizes the influence of the environment on language learning, while cognitivism focuses on the mental processes involved in understanding and producing language. The mentalism school highlights the internal and innate aspects of human language capacity, whereas nativism argues that language ability is inherent. In the context of Arabic language learning, psycholinguistics plays a significant role. The principles from these various schools can be applied to design more effective teaching methods, taking into account student motivation and individual differences. Although each school has a different approach, they all provide important insights into the complexity and mastery of language. This background underscores the necessity of understanding various psycholinguistic approaches to enhance the effectiveness of language teaching and to provide a theoretical foundation for educators in formulating better instructional strategies.